China Pakistan Economic Corridor Digital Transformation - Zhong, Ma; Ali, Majid; Faqir, Khan; Begum, Salma; Haider, Bilal; Shahzad, Khurram; Nosheen, Nosheen (Frontiers in Psychology, 2022)
The Vision and Mission of the China-Pakistan Economic Corridor (CPEC) are to improve the people's living standards of Pakistan and China through bilateral investments, trade, and economic activities. To achieve this envisioned dream, Pakistan set up the China-Pakistan Economic Corridor Authority (CPECA) to further its development, but the Covid-19 slowed it down. This situation compelled the digitization of CPEC. This article reviews the best practices and success stories of various digitization and e-governance programs and, in light of that advised the implementation of the Ajman Digital Governance (ADG) model as a theoretical framework for CPEC digitalization. This article concludes that Pakistan's government needs to transform CPEC digitalization by setting up CPEC Digitization and Transformation Center (DTC) at the CPECA office to attract investors and business.